Eye Injuries among Primary School Children in Enugu, Nigeria: Rural vs Urban. (January 2015) - Okpala, Nonso Ejikeme; Umeh, Rich Enujioke; Onwasigwe, Ernest Nnemeka
A cross-sectional survey of the prevalence of eye injuries among primary school children in two noncontiguous local government areas of Enugu State of Nigeria was undertaken. One of the local government areas was urban, while the other one was rural. Children who were <15 years in two randomly selected primary schools in the urban area and three randomly selected schools in the rural area were interviewed and examined with Snellen chart, pen torch, head loupe, and direct ophthalmoscope. The findings were recorded using a semi-structured questionnaire and the World Health Organization Programme for Prevention of Blindness (WHO/PBL) eye examination form. Training on visual acuity measurement was done for each of the class teachers. A total of 1, 236 children <15 years of age were studied and analyzed. Slightly more females, 652 (52.8%), than males, 584 (47.2%), constituted the sample population giving a female/male ratio of 1.1:1. A total of 98 (7.93%) children had evidence of injury to the eye or its adnexa. Eyelid scar was the commonest (5.34%) followed by eyebrow scar (2.10%). Canthal scar was the next (0.32%). Two girls had monocular blindness from eye trauma (0.16%). One had leucoma, while the other had a dislocated lens. All the monocular blind children of this study were from the urban area. The home was the commonest environment for an eye injury (69.39%) followed by the school (20.41%). The farm was next in frequency (7.14%), especially among boys in the rural area. The church and the road/street constituted the remainder. Regarding persons causing the injury, the child's playmate was the commonest (55.10%) followed by self (27.55%). Parents and guardians were the next (9.18%). These were injuries associated with corporal punishment. Corporal punishment-related eye injury, according to this study, appears to be common in the rural area and affects boys predominantly. Other human intermediary agents that cause an eye injury include passersby (2.04%), RTA (2.04%), siblings (2.04%), and others (1.02%). The primary agents that caused an eye injury were sticks/wood, 29 (29.60%); stone, 21 (21.43%); pieces of metal, 19 (19.39%); fall, 10 (10.20%); fight/fist blow, 9 (9.918%); plastic, 2 (2.04%); fingernails, 2 (2.04%); farm tools/fruits, 2 (2.04%); and RTA, glass, and headbutt, each 1.02%. Farm implements/fruits as well as fingernails appear to be fairly common primary agents that cause an eye injury in the rural Enugu, Nigeria. In terms of prevalence, there was no significant difference between the urban and rural areas. The findings from this study showed a high prevalence of eye injury among primary school children. In terms of treatment, 58.16% of the children with an eye injury had no form of treatment for it. The children from this study with monocular blindness did not receive adequate medical treatment. Treatment of an eye injury, according to this study, was sought from chemists (19.39%), at hospital/health centers (16.33%), at home (3.06%), and from traditional healers (3.06%). The persons who treated an eye injury, as observed from this study, were doctors (14.29%), nurses (4.08%), chemists (17.35%), and traditional healers and fathers (3.06% each). The frequency of noninjury-related diagnosis made in this study was refractive error, 4.85%; allergic conjunctivitis, 1.94%; oculocutaneous albinism, 0.24%; prepapillary vascular loops, 0.40%; and then ptosis, exotropia, stye, corneal opacity, and retinitis pigmentosa, 0.08% each. The annual incidence of an eye injury according to this study was 3.48%. The majority of the causes of an eye injury, as per this study, were preventable. Appropriate promotion of preventive eye care among children may go a long way in reducing the burden of blindness from eye injuries.